Lanti sickness by fright : a Bisayan Filipino peasant syndrome - Hart, Donn V. (Philippine Quarterly of Culture & Society, 1975)
Analysis is focused on the pathogenesis, etiology, preventive measures and therapy associated with a syndrome that in a certain village on the island of Samar (Philippines) is known as Lanti. This sickness results from direct fright of a child (usually the youngest) or fright indirectly transmitted to this child by his parents or other household members. Three lanti curing rites, pagtubod, paglo-on, and pagbirik and their folk medical specialists, are included.